2018
DOI: 10.1038/s41551-018-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle delivery of CRISPR into the brain rescues a mouse model of fragile X syndrome from exaggerated repetitive behaviours

Abstract: Technologies that can safely edit genes in the brains of adult animals may revolutionize the treatment of neurological diseases and the understanding of brain function. Here, we demonstrate that intracranial injection of CRISPR–Gold, a nonviral delivery vehicle for the CRISPR–Cas9 ribonucleoprotein, can edit genes in the brains of adult mice in multiple mouse models. CRISPR–Gold can deliver both Cas9 and Cpf1 ribonucleoproteins, and can edit all of the major cell types in the brain, including neurons, astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
213
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(216 citation statements)
references
References 54 publications
1
213
0
2
Order By: Relevance
“…Furthermore, the marble‐burying assay and the empty cage observation test were implemented in both wild‐type mice and Fmr1 knockout mice to evaluate the repetitive behaviors. It was found that the symptoms of exaggerated repetitive behaviors were alleviated after the administration of CRISPR‐Gold nanoparticles (Figure C, D) …”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the marble‐burying assay and the empty cage observation test were implemented in both wild‐type mice and Fmr1 knockout mice to evaluate the repetitive behaviors. It was found that the symptoms of exaggerated repetitive behaviors were alleviated after the administration of CRISPR‐Gold nanoparticles (Figure C, D) …”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 97%
“…(D) mGluR5‐CRISPR successfully promotes mGluR5 gene editing in the striatum of wild‐type and Fmr1 knockout mice. Reproduced with permission…”
Section: Non‐viral Vectors Of Crispr‐cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have used CRISPR‐based editing to correct the genetic basis of many diseases in isolated cells or animal models . The first wave of clinical trials using CRISPR enzymes to treat inherited disorders in humans involve removing a patient's cells, editing ex vivo, and reinfusing the corrected cells .…”
mentioning
confidence: 99%
“…Researchers have used CRISPR-based editing to correct the genetic basis of many diseases in isolated cells or animal models. [20][21][22][23][24][25][26][27][28][29] The first wave of clinical trials using CRISPR enzymes to treat inherited disorders in humans involve removing a patient's cells, editing ex vivo, and reinfusing the corrected cells. 30 Such ex vivo genome editing is currently the most technically feasible approach, and has the potential to treat devastating blood disorders like sickle cell disease and β-thalassemia.…”
mentioning
confidence: 99%